First Report on the Rapid Detection and Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) in Viable but Non-culturable (VBNC) Under Food Storage Conditions - Ou, Aifen; Wang, Kan; Mao, Yanxiong; Yuan, Lei; Ye, Yanrui; Chen, Ling; Zou, Yimin; Huang, Tengyi (Frontiers in Microbiology, 2021)
Formation of viable but non-culturable (VBNC) status in methicillin-resistant Staphylococcus aureus (MRSA) has never been reported, and it poses a significant concern for food safety. Thus, this study aimed to firstly develop a rapid, cost-effective, and efficient testing method to detect and differentiate MRSA strains in the VBNC state and further apply this in real food samples. Two targets were selected for detection of MRSA and toxin, and rapid isothermal amplification detection assays were developed based on cross-priming amplification methodology. VBNC formation was performed for MRSA strain in both pure culture and in artificially contaminated samples, then propidium monoazide (PMA) treatment was further conducted. Development, optimization, and evaluation of PMA-crossing priming amplification (CPA) were further performed on detection of MRSA in the VBNC state. Finally, application of PMA-CPA was further applied for detection on MRSA in the VBNC state in contaminated food samples. As concluded in this study, formation of the VBNC state in MRSA strains has been verified, then two PMA-CPA assays have been developed and applied to detect MRSA in the VBNC state from pure culture and food samples.